Community attitudes survey, 1995-1996 (UK Data Service, 2004)
The Community Attitudes Survey was first carried out in 1992 following a review of crime survey needs in Northern Ireland. In accordance with the recommendations of the review, the Central Survey Unit (CSU) of the Northern Ireland Statistics and Research Agency (NISRA) was commissioned to conduct a continuous survey of community attitudes towards law and order named the Community Attitudes Survey. The survey measures a broad range of attitudes towards crime, policing and the courts. The main purpose of the survey is to collect people’s opinions about safety in their area, home security measures, crime levels, the police and the courts. Over the years a number of questions have either been dropped from or added to the survey, with the most noticeable change occurring in the third year (1994-1995, SN:4792) when the security questions were dropped. A complete breakdown of the questions and the years in which they were asked is included in the documentation. Another major change occurred in the fifth year (1996-1997, SN:4794) when the annual allocation size was reduced from 3360 to 2400.